Diametrically Opposite Scaling of Extreme Precipitation and Streamflow to Temperature in South and Central Asia. Issue 17 (2nd September 2020) - Ghausi, Sarosh Alam; Ghosh, Subimal
Abstract: Clausius‐Clapeyron (CC) equation suggests a 6–7% increase in extreme precipitation per degree rise in temperature. Scaling rates of extreme precipitation with temperature at different regions significantly deviate from the CC rate. We find that the daily extreme precipitation scaling is negative over sites in the warmer tropical region of South Asia, as opposed to positive scaling over the cooler subtropics. Daily precipitation scaling tends to break down and becomes negative above a temperature of 23–24°C in all the regions. However, such breakdown disappears for subdaily precipitation extremes, and they continue to increase at high temperatures over both tropics and subtropics. This leads to high positive streamflow‐temperature scaling over small catchments, in contrast to extreme precipitation scaling at a daily scale, which is partly negative. Our analysis highlights an increased threat due to flash flood in a warmer climate, which cannot be fully estimated with the analysis of daily precipitation extremes. Plain Language Summary: Clausius‐Clapeyron (CC) equation suggests a rise in atmospheric moisture‐holding capacity by 6–7%/°C. Extreme precipitation events are expected to intensify in response to increased warming, at a similar rate. However, observational evidences show large spatiotemporal variability in the extreme precipitation scaling with significant deviations from the CC rate. Here, we analyzed the sensitivity of extreme precipitation and streamflow with temperature over a large region of South and Central Asia. We found contrasting scaling of daily extreme precipitation and extreme streamflow to increased temperature. Daily precipitation exhibits sub‐CC (<7%) to negative scaling rates whereas extreme streamflows have intensified at rates close to twice CC (10–14%) for small catchments to CC (5–7%) for large catchments. We attribute such inconsistency between daily precipitation and streamflow extremes to increased sensitivity of 3‐hourly precipitation extremes with temperature. We found 3‐hourly extremes to increase with Super CC to CC rates resulting in flash floods over small catchments and leading to large extreme streamflow scaling. Our finding suggests a potential intensification of flash floods in small catchments in changing climate, posing a major threat for community resilience and ecosystem in warming future. Key Points: Contrasting scaling of extreme precipitation and extreme streamflow to increased temperature is found over tropical Asia In South Asia scaling of extreme precipitation‐temperature is CC to super‐CC at subdaily scale, while sub‐CC to negative at daily scale Increased scaling of 3‐hourly rainfall at high temperature leads to positive extreme streamflow‐temperature scaling in small catchments